Pendidikan politik dan politik pendidikan - Sunarso Sunarso (Jurnal Civics: Media Kajian Kewarganegaraan, 2007)
Political education, therefore, as such, has not had a central part in curiculum, although what is often referred to as the hidden curriculum could be argued to have contributed to a political education of sorts, shaping the attitudes of students towards authoriry and implicitlY forming the values of the students in such politicallY important matters as socialjustice, racial and gender equaliry, or nationallqyaliry. But such political formation would be implicit, and indeed the protesters in the 1970s against the exploration in clasrooms of the rights and wrongs of nuclear warfare did not see that their own action enforced a particular political position as the legitimate one to be subscribed to ry teachers. Education and politics are inextricablY linked. Politics is inseparable from education, unless the country plans to generate illiterate politicians' who could not be expected to lead the republi~ out of the current crises. You cannot escape politics or separate it from education. Politics is the way to manage the broad environment, and not merelY a struggle for power. Therefore it is the dury of schools to help students dijJerentiate between good politics and bad politics.